REHABILITATION OF SIEBERTS CLASS III DEFECT WITH DIFFERENT APPROACH (International Journal of Food and Nutritional Sciences, 2022)
Rehabilitation of ridge defect is very challenging task for a Prosthodontics. To achieve proper esthetics and speech, closure of the defect must be done along with replacement of the missing teeth. These defects can be treated with different types of prosthesis but they do not replace the exactly lost soft tissue structures. Complete Implant-supported rehabilitation have great successful rate, but they have questionable prognosis in case of type three Siebert ridge defects. In this types cases the Andrew's bar system can be one of the best options for patient. Basically, Andrew’s bridge is a type of fixed-removable types of prosthesis and fulfills all the requirements of the patient like structural, functional and esthetic. Fixed-removable partial prosthesis is mainly indicated for patients with excessive soft tissue loss and when the alignment of the opposing arches creates difficulties for placement of a conventional fixed partial denture. In this article presents a case report that describes need of fixed-removable types of prosthesis and various step involve in fabrication of fixed-removable types of prosthesis to treat a Siebert’s Class III anterior ridge defect using natural teeth as abutments for its fixed component followed by a removable component. Andrew's bar system provides a more reliable alternative method as compare to implants in cases both soft and hard tissue defect.